Formation Of Ceria Buffer Layer For Yba2cu3o7-X Superconductors - Lim, Shu Lee (2010)
CeO2 films were formed on rolling-assisted-biaxially-textured (RABiT) Ni and Cu substrates by chemical solution deposition (CSD) method via metal organic decomposition (MOD) route. The CeO2 film is to be used as a buffer layer for YBCO coated conductor application. Experimental parameters that were carried out were the concentration of Ce precursor solution, type of solvent used, volume percent of methanol and annealing treatment process: the temperature, time and atmosphere.The precursor solution used was cerium(III) acetate dissolved in either propionic acid or acetic acid and added with methanol. The precursor solution was spin coated on the substrate at the speed of 4000 rpm and followed by annealing. The homogeneous, crack free and epitaxial CeO2 film was produced on RABiT Ni by using 0.30 mol/l Ce precursor solution added with 20 vol% methanol and annealed in Ar-5%H2 for an hour at 1000oC. No interfacial layer between the CeO2 layer and Ni substrate was observed. The thickness of the film was estimated to be 25 nm and the adherency of the film on the substrate was good. Typical roughness, in RMS of the film was 7 nm. On the other hand, on RABiT Cu, severe interfacial reaction was seen. Samples annealed in Ar-5%H2 for an hour at 1000oC are consisted of CeO2 (surface layer) | Cu2O (nodules) | Cu2O (compact) on Cu. When the surface layer and the porous nodules were etched, a flat (200) Cu2O film was seen. Samples annealed in vacuum for an hour at 1000 oC are consisted of CeO2 (surface layer) | reduced CeO2 (compact)on Cu. The formation of the layered oxides on Cu in Ar-5%H2 and vacuum were proposed.